A method for preparing graphite / aluminum composite material for heat spreaders

By adding copper-plated scale graphite to the graphite/aluminum composite material and performing hot pressing molding, the problems of poor compatibility and intermediate phase generation of composite materials are solved, and the effects of high density, strong mechanical properties and excellent thermal conductivity are achieved.

CN119776693APending Publication Date: 2025-04-08TAIYUAN AERO INSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411762945.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

There are problems of poor physical, chemical, mechanical compatibility between graphite and aluminum, resulting in weak interface bonding and poor density of composite materials, and easy to generate the mesophase Al4C3 at high temperatures, reducing the mechanical and thermal conductivity of composite materials.

Method used

By adding copper-plated scale graphite to the composite material and optimizing the hot pressing process, the formation of the Al4C3 interface is suppressed and the density and thermal conductivity of the composite material are improved.

Benefits of technology

The advantages of good denseness, high mechanical strength and good thermal conductivity of graphite/aluminum composites are achieved, which are specifically manifested in improving the lateral and longitudinal thermal conductivity of the composite materials, enhancing its mechanical properties, and optimizing the production process to reduce the sintering temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776693A_ABST
    Figure CN119776693A_ABST
Patent Text Reader

Abstract

This invention belongs to the technical field of graphite metal composite materials and discloses a method for preparing a graphite / aluminum composite material for a heat spreader. The method includes: obtaining two types of natural flake graphite with a first natural flake graphite particle size larger than that of a second natural flake graphite; electroplating copper onto the first natural flake graphite to obtain copper-plated flake graphite; mixing the copper-plated flake graphite, the second natural flake graphite, and aluminum powder in different mass ratios to obtain a first powder and a second powder; compacting a portion of the first powder in a graphite mold, then spreading the second powder on its upper surface; spreading another portion of the first powder on the upper surface of the second powder; and hot-pressing to obtain the graphite / aluminum composite material. The graphite / aluminum composite material of this invention has advantages such as good density, high mechanical strength, and good thermal conductivity. This material can be used to process components and has a broad application market in the thermal management of high-power heating elements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite metal composite materials, and specifically relates to a method for preparing a graphite / aluminum composite material for a temperature equalizing plate. Background Art

[0002] Thermal management technology is one of the most critical technologies for future combat aircraft, and is also an essential technical support for the development of other military applications such as aviation, aerospace, and missile-borne, as well as civilian applications such as electric vehicles and base stations. In recent years, electronic equipment has gradually developed in the direction of miniaturization, high frequency, and high power, which has led to a surge in equipment heat generation, which can easily cause the core components to overheat and form hot spots. If the heat at the hot spot is not dissipated in time, it will affect the reliability and stability of the equipment, and may even cause the equipment to fail. Therefore, heat dissipation technology has become one of the key issues that determine the effectiveness and reliability of electronic equipment operation.

[0003] At present, the commonly used heat dissipation methods include air cooling, liquid cooling, and phase change temperature equalization. Among them, air cooling technology is difficult to meet application requirements when facing high-heat-generating devices, and the noise is relatively high; liquid cooling technology is prone to problems such as flow channel corrosion and changes in the pH value of the coolant; phase change temperature equalization technology is prone to failure due to problems such as uneven phase change and local evaporation under conditions of large overload or structural limitations, poor back-end heat dissipation conditions, etc. In comparison, solid-state temperature equalization boards can solve problems such as air cooling being unable to achieve low noise, liquid cooling liquid medium deterioration and corrosion, and phase change temperature equalization being prone to failure. Temperature equalization boards based on solid-state thermal conductive materials are the most effective thermal management solution for board-level heat dissipation of high-power electronic equipment.

[0004] Composite materials can give full play to the advantages of different materials, such as graphite materials 2 The structure provides a perfect phonon transmission channel and has the advantage of high thermal conductivity. Using it as a thermal conductive matrix for composite materials can effectively improve the thermal conductivity of composite materials. Among metal materials, silver, copper, and aluminum have excellent thermal conductivity. Considering factors such as economy and weight, aluminum has more advantages as a metal matrix in composite materials. Graphite / aluminum composite materials can give full play to the high thermal conductivity of graphite and the high mechanical strength of aluminum matrix while achieving lightweight characteristics. They are the best choice for composite thermal conductive materials for heat spreaders.

[0005] Although graphite has excellent thermal conductivity and is an ideal filler for metal-based composites, there is a large physical, chemical, and mechanical compatibility problem between graphite and aluminum. Graphite and aluminum have poor wettability, and the wetting angle can reach 140°, which makes the prepared composite material weak in interface bonding and poor in density. Graphite and aluminum are prone to generate an intermediate phase Al4C3 at high temperatures. This substance is easily soluble in water and brittle, which will reduce the mechanical properties of the composite material. Graphite materials mainly conduct heat through phonons, while aluminum materials mainly conduct heat through electrons, and the elastic-plastic deformation characteristics of graphite and aluminum are quite different, which leads to the thermal conductivity and mechanical properties of the composite material being far from the ideal value.

[0006] Therefore, effectively inhibiting the generation of harmful intermediate phases, filling the gap between graphite and aluminum matrix, optimizing the processability of composite materials, and improving the thermal conductivity and mechanical properties of composite materials are the keys to realizing the application of graphite / aluminum composite materials. Summary of the invention

[0007] In order to effectively inhibit the generation of the intermediate phase between graphite and aluminum, fill the gap between graphite and aluminum, and improve the density of the composite material, the present invention discloses a method for preparing a graphite / aluminum composite material for a temperature equalizing plate, and the preparation method comprises the following steps:

[0008] S1. Obtaining a first natural flake graphite and a second natural flake graphite, wherein the particle size of the first natural flake graphite is larger than the particle size of the second natural flake graphite;

[0009] S2, plating copper on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite;

[0010] S3, mixing the copper-plated flake graphite, the second natural flake graphite and aluminum powder in different mass ratios to obtain a first powder and a second powder, and dividing the first powder into two parts;

[0011] S4, spreading a portion of the first powder in a graphite mold and compacting it to form a lower matrix, spreading the second powder on the upper surface of the lower matrix to form a middle matrix, and spreading another portion of the first powder on the upper surface of the middle matrix to form an upper matrix;

[0012] S5, hot pressing the composite matrix of step S4 to obtain a graphite / aluminum composite material, and milling the graphite / aluminum composite material to prepare for subsequent processing of a temperature equalizing plate.

[0013] Furthermore, in step S1, the particle size of the first natural flake graphite is 100-300 meshes, and the particle size of the second natural flake graphite is 30-200 meshes.

[0014] Further, in step S2, copper is plated on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite, comprising:

[0015] The first natural flake graphite is sequentially subjected to degreasing treatment, hydrophilization treatment, roughening treatment, sensitization treatment, activation treatment, reduction treatment and copper plating treatment to obtain copper-plated flake graphite.

[0016] Furthermore, in step S2, the mass fraction of copper in the copper-plated flake graphite is 35% to 71%.

[0017] Furthermore, in step S3, the mass fractions of aluminum powder and flake graphite in the first powder are 80% to 100% and 0% to 20% respectively, the mass fractions of aluminum powder and flake graphite in the second powder are 15% to 60% and 40% to 85% respectively, and the mass ratios of the copper-plated flake graphite in the flake graphite in the first powder and the second powder to the second natural flake graphite are both 1:05 to 1:20.

[0018] Furthermore, in step S3, the aluminum powder includes pure aluminum powder or alloy aluminum powder, and the particle size of the aluminum powder is 1 to 50 μm.

[0019] Furthermore, in step S5, the process parameters of hot pressing molding include sintering temperature of 530-640°C, pressure of 20-40 MPa, heating rate of 5-10°C / min and holding time of 10-40 min.

[0020] Furthermore, in step S5, the mass ratio of the first powder to the second powder in the prepared graphite / aluminum composite material is 1:1 to 1:20.

[0021] Compared with the prior art, the beneficial effects that can be achieved by at least one of the above technical solutions adopted in the embodiments of this specification include at least: the graphite / aluminum composite material for the temperature equalizing plate prepared by the method of the present invention has the advantages of good density, high mechanical strength and good thermal conductivity, specifically:

[0022] (1) By adding copper-plated flake graphite to the composite material, the wettability of graphite and aluminum is improved, and the gap between large-diameter graphite and aluminum powder can be effectively filled, thereby improving the density of the composite material;

[0023] (2) By adding copper-plated flake graphite to the composite material and optimizing the hot pressing process, the formation of Al4C3 interface is effectively suppressed and the thermal conductivity of the composite material is improved;

[0024] (3) By adding copper elements to the composite material, the diffusion of copper elements to aluminum elements during high-temperature sintering promotes the movement of graphite elements, which is beneficial to improving the mechanical strength of the composite material;

[0025] (4) The raw material ratio of the copper-plated flake graphite, the second natural flake graphite and the aluminum powder is controlled, the production process is optimized, and a dense composite material can be obtained at a lower sintering temperature.

[0026] (5) Through a special powder spreading process, for example, the mold can be adaptively designed according to the product configuration requirements to change the spatial distribution of the first powder and the second powder in the product, so that the prepared graphite / aluminum composite material can be milled and welded, and can be directly used as a temperature equalizing plate device, which has good practical value.

[0027] The density of the graphite / aluminum composite material prepared by the method of the present invention is 2.1-2.6 g / cm 3 The lateral thermal conductivity reaches 613W / (m·K), and the longitudinal thermal conductivity can reach 42W / (m·K). BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 The figure is a flow chart of the preparation of the graphite / aluminum composite material disclosed in the embodiment of the present invention;

[0030] Figure 2 A longitudinal metallographic image of a graphite / aluminum composite material disclosed in an embodiment of the present invention;

[0031] Figure 3 This is a SEM image of the graphite / aluminum composite material disclosed in the embodiment of the present invention;

[0032] Figure 4 A line scan of the graphite / aluminum composite material disclosed in an embodiment of the present invention;

[0033] Figure 5 This is an X-ray diffraction diagram of the graphite / aluminum composite material disclosed in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0035] The following describes the implementation methods of the present application through specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present application from the content disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The present application can also be implemented or applied through other different specific implementation methods, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present application. It should be noted that the following embodiments and the features of the embodiments can be combined with each other in the absence of conflict. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present application.

[0036] In the description of this embodiment, it is necessary to understand that the orientations or positional relationships indicated by the terms "upper layer", "middle layer", "lower layer", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the invention and simplifying the description, rather than indicating or implying that the product referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the invention.

[0037] In addition, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more features. In the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0038] The first embodiment of this specific implementation method discloses a method for preparing a graphite / aluminum composite material for a temperature plate, see Figure 1 As shown, the preparation method comprises the following steps:

[0039] S1. Obtain a first natural flake graphite and a second natural flake graphite, wherein the particle size of the first natural flake graphite is greater than the particle size of the second natural flake graphite, wherein the particle size of the first natural flake graphite is 100-300 meshes, and the particle size of the second natural flake graphite is 30-200 meshes.

[0040] S2. Copper is plated on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite, wherein the mass fraction of copper in the copper-plated flake graphite is 35% to 71%.

[0041] The specific process of copper plating on the first natural flake graphite is as follows: degreasing treatment is diluted H2SO4 treatment for 30 minutes; hydrophilization treatment is boiling in a 5g / L NaOH solution for 10 minutes, and then washing with distilled water until neutral; roughening treatment is boiling in a 10% HNO3 solution for 10 minutes, and then washing with distilled water until neutral; the purpose of sensitization treatment is to form Sn with reducing ability on the surface of natural flake graphite. 2+ Specifically, the roughened natural flake graphite was added to a solution with a SnCl2 concentration of 10 g / L and a HCl concentration of 20 mL / L and stirred for 5 min, and then washed with distilled water until neutral; the purpose of the activation treatment was to form a catalytic center Pd on the surface of the natural flake graphite, and the sensitized natural flake graphite was added to the PdC l2 concentration of 0.25g / L, HCl concentration of 20mL / L solution stirred for 5min, and then washed with distilled water to neutral; the reduction process is to activate the natural flake graphite in the concentration of 30g / L, the temperature of 30 ℃ NaH2PO2 solution stirred for 15min, and then washed with distilled water to neutral and dried; copper plating process of the plating solution is 20g / L CuSO4 5H2O, 25mL / L HCHO, 25g / L Na2EDTA, 14g / L C4H4KNa 4H2O, 20mg / L 2-2 'bipyridine, the temperature is 50 ℃, the loading amount is 6g / L, with NaOH to adjust the pH to 12, and the magnetic stirring method is used for stirring, the stirring speed is 600r / min, the thickness of the copper coating is controlled by the reaction time, the time is 10 to 30min; finally, washed with distilled water, filtered, and dried.

[0042] S3, the copper-plated flake graphite, the second natural flake graphite and aluminum powder are mixed in a mass ratio to obtain a second powder. The mass fractions of aluminum powder and flake graphite in the second powder are 15% to 60% and 40% to 85%, respectively, wherein the mass ratio of the copper-plated flake graphite to the second natural flake graphite in the flake graphite in the second powder is 1:05 to 1:20. The aluminum powder includes pure aluminum powder or alloy aluminum powder, and the particle size of the aluminum powder is 1 to 50 μm. When mixing several raw materials, the rotation speed is controlled to 400 to 600 r / min, and the mixing time is controlled to 5 to 20 min.

[0043] S4. Spread the second powder in a graphite mold and perform hot pressing to obtain a graphite / aluminum composite material. Mill the graphite / aluminum composite material to prepare for subsequent temperature equalizing plate processing. The process parameters of hot pressing are a sintering temperature of 530 to 640°C, a pressure of 20 to 40 MPa, a heating rate of 5 to 10°C / min, and a holding time of 10 to 40 min. The mass ratio of the first powder to the second powder in the obtained graphite / aluminum composite material is 1:1 to 1:20.

[0044] The second embodiment of this specific implementation method discloses a method for preparing a graphite / aluminum composite material for a temperature plate, see Figure 1 As shown, the preparation method comprises the following steps:

[0045] S1. Obtain a first natural flake graphite and a second natural flake graphite, wherein the particle size of the first natural flake graphite is greater than the particle size of the second natural flake graphite, wherein the particle size of the first natural flake graphite is 100-300 meshes, and the particle size of the second natural flake graphite is 30-200 meshes.

[0046] S2. Copper is plated on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite, wherein the mass fraction of copper in the copper-plated flake graphite is 35% to 71%.

[0047] S3. Mix the copper-plated flake graphite, the second natural flake graphite and aluminum powder in different mass ratios to obtain a first powder and a second powder, and divide the first powder into two parts.

[0048] The first powder can be divided into two parts evenly or into two different parts according to the requirements; the mass fractions of aluminum powder and flake graphite in the first powder are 80% to 100% and 0% to 20% respectively, and the mass fractions of aluminum powder and flake graphite in the second powder are 15% to 60% and 40% to 85% respectively, wherein the mass ratio of the copper-plated flake graphite in the flake graphite in the first powder and the second powder to the second natural flake graphite is 1:05 to 1:20. The aluminum powder includes pure aluminum powder or alloy aluminum powder, and the particle size of the aluminum powder is 1 to 50 μm.

[0049] S4, spreading a portion of the first powder in a graphite mold and compacting it to form a lower matrix, spreading the second powder on the upper surface of the lower matrix to form a middle matrix, and spreading another portion of the first powder on the upper surface of the middle matrix to form an upper matrix;

[0050] S5. The composite matrix of step S4 is hot-pressed to obtain a graphite / aluminum composite material, and the graphite / aluminum composite material is milled to form it for subsequent temperature equalizing plate processing, wherein the process parameters of the hot-pressing forming are a sintering temperature of 530-640°C, a pressure of 20-40 MPa, a heating rate of 5-10°C / min, and a holding time of 10-40 min. The mass ratio of the first powder to the second powder in the obtained graphite / aluminum composite material is 1:1-1:20.

[0051] This specific embodiment adopts the preparation method disclosed in the first embodiment to screen the raw materials for preparing the graphite / aluminum composite material through the following examples 1 to 14, and at the same time compares the graphite / aluminum composite materials prepared by examples 1 to 14 with comparative examples 1 to 3.

[0052] Example 1: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0053] S1, screening natural flake graphite with particle sizes of 250 mesh and 30 mesh;

[0054] S2, using a chemical plating method to plate Cu on the surface of the 250-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0055] S3, mixing the natural flake graphite powder with a particle size of 30 mesh screened in step S1, the copper-plated flake graphite in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:7;

[0056] S4, putting the mixed powder obtained in step S3 into a graphite mold, and putting it into a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560°C, the heating rate is 5°C / min, the temperature is kept for 20 minutes, the pressure is kept at 35MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material

[0057] Example 2: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0058] S1, screening natural flake graphite with particle sizes of 100 mesh and 80 mesh;

[0059] S2, using a chemical plating method to plate Cu on the surface of the 100-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0060] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 20 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:3;

[0061] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 minutes, the pressure is maintained at 35 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0062] Example 3: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0063] S1, screening natural flake graphite with particle sizes of 250 mesh and 100 mesh;

[0064] S2, using a chemical plating method to plate Cu on the surface of the 250-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 10 minutes, and the copper mass content is 35%;

[0065] S3, mixing the natural flake graphite powder with a particle size of 100 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 1 μm under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 10 min, and finally obtaining a mixed powder, wherein the mass content of aluminum powder in the mixed powder is 20%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:0.5;

[0066] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 580° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 40 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0067] Example 4: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0068] S1, screening natural flake graphite with particle sizes of 100 mesh and 80 mesh;

[0069] S2, using a chemical plating method to plate Cu on the surface of the 100-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0070] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 20 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:20;

[0071] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 10° C. / min, the temperature is kept for 20 minutes, the pressure is maintained at 35 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0072] Example 5: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0073] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0074] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0075] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0076] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0077] Example 6: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0078] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0079] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0080] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 50 μm under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 15 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 20%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:5;

[0081] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 610° C., the heating rate is 5° C. / min, the temperature is kept for 30 minutes, the pressure is maintained at 35 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0082] Example 7: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0083] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0084] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0085] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0086] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 640° C., the heating rate is 10° C. / min, the temperature is kept for 20 minutes, the pressure is maintained at 35 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0087] Example 8: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0088] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0089] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0090] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0091] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 530° C., the heating rate is 5° C. / min, the temperature is kept for 30 min, the pressure is maintained at 40 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0092] Example 9: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0093] S1, screening natural flake graphite with particle sizes of 300 mesh and 150 mesh;

[0094] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0095] S3, mixing the natural flake graphite powder with a particle size of 150 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 25 μm under vacuum conditions, wherein the rotation speed is 400 r / min, and the time is 20 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 30%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:8;

[0096] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 570°C, the heating rate is 5°C / min, the temperature is kept for 30 minutes, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0097] Example 10: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0098] S1, screening natural flake graphite with particle sizes of 300 mesh and 200 mesh;

[0099] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0100] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 1 μm under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 20 min, and finally obtaining a mixed powder, wherein the mass content of aluminum powder in the mixed powder is 30%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:15;

[0101] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 570°C, the heating rate is 5°C / min, the temperature is kept for 30 minutes, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0102] Example 11: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0103] S1, screening natural flake graphite with particle sizes of 200 mesh and 80 mesh;

[0104] S2, using a chemical plating method to plate Cu on the surface of the 200-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 30 minutes, and the copper mass content is 71%;

[0105] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 20 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 15%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0106] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 10 min, the pressure is kept at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0107] Example 12: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0108] S1, screening natural flake graphite with particle sizes of 200 mesh and 80 mesh;

[0109] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0110] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 10 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 50%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0111] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0112] Example 13: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0113] S1, screening natural flake graphite with particle sizes of 300 mesh and 200 mesh;

[0114] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0115] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 1 μm under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 20 min, and finally obtaining a mixed powder, wherein the mass content of aluminum powder in the mixed powder is 60%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0116] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0117] Example 14: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0118] S1, screening natural flake graphite with particle sizes of 100 mesh and 80 mesh;

[0119] S2, using a chemical plating method to plate Cu on the surface of the 100-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 30 minutes, and the copper mass content is 71%;

[0120] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 30 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 10 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 15%, and the mass ratio of copper-plated graphite to natural flake graphite is 1:9;

[0121] S4. The mixed powder obtained in step S3 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 10 min, the pressure is maintained at 30 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0122] Comparative Example 1: A method for preparing a graphite / aluminum composite material for a temperature-homing plate, comprising the following steps:

[0123] S1, screening natural flake graphite with a particle size of 80 mesh;

[0124] S2, mixing the natural flake graphite powder with a particle size of 80 mesh and the aluminum powder / alloy aluminum powder with a particle size of 3 μm uniformly under vacuum conditions, wherein the rotation speed is 500 r / min, and the time is 20 min, and finally obtaining a mixed powder, wherein the aluminum powder mass content in the mixed powder is 25%;

[0125] S3. The mixed powder obtained in step S2 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0126] Comparative Example 2: A method for preparing a graphite / aluminum composite material for a temperature-homing plate, comprising the following steps:

[0127] S1, screening natural flake graphite with a particle size of 30 mesh;

[0128] S2, mixing the natural flake graphite powder with a particle size of 80 mesh and the aluminum powder / alloy aluminum powder with a particle size of 25 μm uniformly under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 10 min, and finally obtaining a mixed powder, wherein the aluminum powder mass content in the mixed powder is 50%;

[0129] S3. The mixed powder obtained in step S2 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 620° C., the heating rate is 5° C. / min, the temperature is kept for 40 minutes, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0130] Comparative Example 3: A method for preparing a graphite / aluminum composite material for a temperature-homing plate, comprising the following steps:

[0131] S1, screening natural flake graphite with a particle size of 80 mesh;

[0132] S2, mixing the natural flake graphite powder with a particle size of 80 mesh, the electrolytic copper powder with a particle size of 50 μm, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm uniformly under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 5 min, and finally a mixed powder is obtained, wherein the mass content of aluminum powder in the mixed powder is 25%, and the mass content of electrolytic copper powder is 4%;

[0133] S3. The mixed powder obtained in step S2 is loaded into a graphite mold and placed in a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560° C., the heating rate is 5° C. / min, the temperature is kept for 20 min, the pressure is maintained at 25 MPa, and the mixed powder is taken out after cooling to obtain a graphite / aluminum composite material.

[0134] For the graphite / aluminum composite materials obtained in Examples 1 to 14 and Comparative Examples 1 to 3, their theoretical densities were calculated, and their density, thermal conductivity, and mechanical strength were tested. The test results are shown in Table 1 below:

[0135] Table 1: Performance test table of graphite / aluminum composite materials

[0136]

[0137]

[0138] This specific embodiment uses the raw material ratio and process parameters in the above Example 5 as a reference for the second powder, and prepares the heterogeneous graphite / aluminum composite material through the following Examples a to d as follows:

[0139] Example A: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0140] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0141] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0142] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 minutes, and finally obtaining the second powder and the first powder. The mass ratio of the copper-plated graphite to the natural flake graphite in the mixed powder is 1:9, wherein the mass content of aluminum powder in the second powder is 80%, the mass content of aluminum powder in the first powder is 25%, and the mass ratio of the second powder to the first powder is 1:1;

[0143] S4, putting half of the mixed first powder obtained in step S3 into a graphite mold, and compacting it into a certain shape with the mold;

[0144] S5. Put the second powder obtained in step S3 into the mold of step S4, add the remaining first powder, and put it into a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560°C, the heating rate is 5°C / min, the temperature is kept for 20 minutes, the pressure is maintained at 25MPa, and it is taken out after cooling to obtain a graphite / aluminum composite material.

[0145] Example b: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0146] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0147] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0148] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 minutes, and finally obtaining the second powder and the first powder. The mass ratio of the copper-plated graphite to the natural flake graphite in the mixed powder is 1:9, wherein the mass content of aluminum powder in the second powder is 90%, the mass content of aluminum powder in the first powder is 25%, and the mass ratio of the second powder to the first powder is 1:5;

[0149] S4, putting half of the mixed first powder obtained in step S3 into a graphite mold, and compacting it into a certain shape with the mold;

[0150] S5. Put the second powder obtained in step S3 into the mold of step S4, add the remaining first powder, and put it into a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560°C, the heating rate is 5°C / min, the temperature is kept for 20 minutes, the pressure is maintained at 25MPa, and it is taken out after cooling to obtain a graphite / aluminum composite material.

[0151] Example c: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0152] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0153] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0154] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 min, and finally obtaining the first powder. The mass ratio of the copper-plated graphite to the natural flake graphite in the mixed powder is 1:9, the mass content of the aluminum powder in the first powder is 25%, wherein the mass content of the aluminum powder in the first powder is 100%, and the mass ratio of the first powder to the first powder is 1:20;

[0155] S4, putting half of the mixed first powder obtained in step S3 into a graphite mold, and compacting it into a certain shape with the mold;

[0156] S5. Put the second powder obtained in step S3 into the mold of step S4, add the remaining first powder, and put it into a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560°C, the heating rate is 5°C / min, the temperature is kept for 20 minutes, the pressure is maintained at 25MPa, and it is taken out after cooling to obtain a graphite / aluminum composite material.

[0157] Example d: A method for preparing a graphite / aluminum composite material for a temperature homogenizing plate, comprising the following steps:

[0158] S1, screening natural flake graphite with particle sizes of 300 mesh and 80 mesh;

[0159] S2, using a chemical plating method to plate Cu on the surface of the 300-mesh natural flake graphite obtained in step S1 to obtain copper-plated flake graphite, the copper plating time is 15 minutes, and the copper mass content is 50%;

[0160] S3, mixing the natural flake graphite powder with a particle size of 80 mesh screened in step S1, the copper-plated flake graphite obtained in step S2, and the aluminum powder / alloy aluminum powder with a particle size of 3 μm under vacuum conditions, wherein the rotation speed is 600 r / min, and the time is 8 minutes, and finally obtaining the second powder and the first powder. The mass ratio of the copper-plated graphite to the natural flake graphite in the mixed powder is 1:9, wherein the mass content of aluminum powder in the second powder is 85%, the mass content of aluminum powder in the first powder is 25%, and the mass ratio of the second powder to the first powder is 1:10;

[0161] S4, putting half of the mixed first powder obtained in step S3 into a graphite mold, and compacting it into a certain shape with the mold;

[0162] S5. Put the second powder obtained in step S3 into the mold of step S4, add the remaining first powder, and put it into a vacuum hot pressing furnace for hot pressing molding, wherein the sintering temperature is 560°C, the heating rate is 5°C / min, the temperature is kept for 20 minutes, the pressure is maintained at 25MPa, and it is taken out after cooling to obtain a graphite / aluminum composite material.

[0163] For the heterogeneous graphite / aluminum composite material obtained in Examples a to d of the present invention, the longitudinal metallographic images are shown in Figure 2 As shown, the SEM image and the corresponding line scan image can be found in Figure 3 and Figure 4 As shown, the X-ray diffraction pattern is shown in Figure 5 As shown, the theoretical density of the graphite / aluminum composite material, its actual density, thermal conductivity, and mechanical strength (i.e., flexural strength) are tested, and the test results are shown in Table 2 below:

[0164] Table 2: Performance test table of heterogeneous graphite / aluminum composite materials

[0165]

[0166]

[0167] The graphite / aluminum composite material for a temperature equalizing plate prepared by the method of the present invention has the advantages of good density, high mechanical strength and good thermal conductivity.

[0168] Obviously, those skilled in the art should understand that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the embodiments of the present invention may have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0169] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a graphite / aluminum composite material for a temperature equalizing plate, characterized in that: The preparation method comprises: Obtaining a first natural flake graphite and a second natural flake graphite, wherein the particle size of the first natural flake graphite is larger than the particle size of the second natural flake graphite, and plating copper on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite; The copper-plated flake graphite, the second natural flake graphite and aluminum powder are mixed in different mass ratios to obtain a first powder and a second powder, and the first powder is divided into two parts; A portion of the first powder is spread flat in a graphite mold and compacted to form a lower matrix, the second powder is spread flat on the upper surface of the lower matrix to form a middle matrix, and another portion of the first powder is spread flat on the upper surface of the middle matrix to form an upper matrix, and hot pressing is performed to obtain a graphite / aluminum composite material.

2. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The particle size of the first natural flake graphite is 100-300 meshes, and the particle size of the second natural flake graphite is 30-200 meshes.

3. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The method comprises plating copper on the first natural flake graphite by chemical plating technology to obtain copper-plated flake graphite, comprising: The first natural flake graphite is sequentially subjected to degreasing treatment, hydrophilization treatment, roughening treatment, sensitization treatment, activation treatment, reduction treatment and copper plating treatment to obtain copper-plated flake graphite.

4. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The mass fraction of copper in the copper-plated flake graphite is 35% to 71%.

5. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The mass fractions of aluminum powder and flake graphite in the first powder are 80% to 100% and 0% to 20% respectively, the mass fractions of aluminum powder and flake graphite in the second powder are 15% to 60% and 40% to 85% respectively, and the mass ratios of the copper-plated flake graphite in the flake graphite in the first powder and the second powder to the second natural flake graphite are both 1:05 to 1:

20.

6. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The aluminum powder includes pure aluminum powder or alloy aluminum powder, and the particle size of the aluminum powder is 1 to 50 μm.

7. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to claim 1, characterized in that: The process parameters of hot pressing include sintering temperature of 530-640°C and pressure of 20-40MPa.

8. The method for preparing the graphite / aluminum composite material for a temperature equalizing plate according to any one of claims 1 to 7, characterized in that: The mass ratio of the first powder to the second powder in the graphite / aluminum composite material is 1:1 to 1:20.